2022
DOI: 10.1371/journal.pone.0262324
|View full text |Cite
|
Sign up to set email alerts
|

Gender sensitivity and stereotypes in medical university students: An Italian cross-sectional study

Abstract: Gender medicine is crucial to reduce health inequalities. Knowledge about students’ attitudes and beliefs regarding men, women and gender is important to improve gender medicine courses. The aim of this study is to evaluate gender stereotypes and its predictors in Italian medical students. We performed an online cross-sectional study among students from the University of Turin. We used the validated Nijmegen Gender Awareness Scale in Medicine scale to explore gender sensitivity and stereotypes. Multivariable l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
2
10
2
Order By: Relevance
“…The GS score was found to be 3.11 (men = 3.14; women = 3.10) among the Indian medical UG students in the present study. Medical students from Switzerland (men = 3.70; women = 3.62) [16], Sweden (men = 3.30; women = 3.37) [18], the Netherlands (men = 3.42; women = 3.43) [18], and Italy (men = 3.73; women = 3.86) [19] reported greater gender sensitivity than the Indian students in the present study. While the mean GRIP and GRID scores in the present study were 2.56 and 2.56, the scores for Swiss medical students showed that they harboured lesser gender stereotyping towards patients (1.92) as well as doctors (2.11) [16].…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…The GS score was found to be 3.11 (men = 3.14; women = 3.10) among the Indian medical UG students in the present study. Medical students from Switzerland (men = 3.70; women = 3.62) [16], Sweden (men = 3.30; women = 3.37) [18], the Netherlands (men = 3.42; women = 3.43) [18], and Italy (men = 3.73; women = 3.86) [19] reported greater gender sensitivity than the Indian students in the present study. While the mean GRIP and GRID scores in the present study were 2.56 and 2.56, the scores for Swiss medical students showed that they harboured lesser gender stereotyping towards patients (1.92) as well as doctors (2.11) [16].…”
Section: Discussioncontrasting
confidence: 45%
“…Gender stereotyping among medical students varied between countries as well [18]. Lower levels of gender stereotyping were linked to older age, more familiarity with gender medicine, and having had a teacher who took gender into account [19]. The above studies showed varied perceptions and levels of gender awareness among different countries, emphasising the importance of cultural effects on gender attitudes among medical students.…”
Section: Introductionmentioning
confidence: 89%
“…Among our sample, women were more likely to perceive their gender as a hurdle to the advancement of their career. Due to them being victims of gender inequalities and sufferers of its consequences, women have an increased sensitivity to gender awareness and its associated issues [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Integration of gender theory is therefore considered necessary to empower female nursing students, make them aware of sociocultural gender roles and how to overcome them and thus improve their professional competence (Andrew et al, 2023). Verdonk et al (2018) developed the Nijmegen Gender Awareness Scale that was used in several countries for medical students, e.g., in Portugal (Morais et al, 2020), Sweden (Andersson et al, 2012), Switzerland (Rrustemi et al, 2020) as well as in Italy (Bert et al, 2022) and was also applied for nursing science (Aliri et al, 2022). The studies showed that gender awareness increases during medical studies and that male students have more stereotypes (Rrustemi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%